Think Pair Share Type Cooperative Learning to Improve Chemistry Learning Outcomes on Atomic Structure Material - Afrida Afrida; Franklin Nwanya; Fouz M. Omar (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The purpose of this research is to improve student learning outcomes in learning atomic structure at Dar El Hikmah Pekanbaru Vocational School by using the think pair share type cooperative learning method. Methodology: The subjects of this research were 24 class X students majoring in Information Technology at Dar El Hikmah Vocational School, Pekanbaru, consisting of female students. In carrying out this classroom action research, there are two types of data collected by researchers, namely quantitative data and qualitative data. This research data collection technique uses tests, observation and interviews. The data analysis technique for this research was analyzed descriptively using the percentage technique of students' absorption of the material per cycle. Main Findings: The results of data analysis show that in general students' absorption of learning material shows an increase, this is based on the evaluation results of 61.7% who have not reached the minimum completeness criteria in cycle I, increasing to 67.54% in cycle II and increasing again to 76.7% in cycle III. The average value of daily test results has also increased. This is shown by the average daily class test results from 60.6, which had not yet reached the minimum completeness criteria score in the previous year, to 73.33 after implementing Think Pair Share type cooperative learning. From the research results it can be concluded that implementing Think Pair Share type cooperative learning can improve student learning outcomes. Novelty/Originality of this study: The novelty of this research is to determine the effectiveness of implementing Think Pair Share type cooperative learning to improve chemistry learning outcomes regarding atomic structure.